An artistic paint having an anti-graffiti stain resistant coating and a method of making the same
By modifying inorganic pigments and nano-silica to create a micro-nano dual rough structure and a high cross-linking density coating, the problems of anti-graffiti, weather resistance, and interface compatibility of UV-cured coatings are solved, resulting in artistic coatings with high decorative and stain-resistant properties.
Patent Information
- Application Number
- CN202611047027.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-15
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2046-07-15
AI Technical Summary
Existing UV-cured coatings have shortcomings in terms of anti-graffiti performance, weather resistance and interfacial compatibility. In particular, they have poor resistance to graffiti media such as oil-based markers and spray paints. Organic pigments are easily degraded, and the migration behavior of low surface energy modification technology in UV curing systems is difficult to control. Furthermore, inorganic pigments have poor compatibility with resins.
A micro-nano dual rough structure was constructed by using spinel-type CoAl2O4 blue pigment for surface modification, combined with silane-modified nano-silica and fluorinated acrylate oligomers. Fluorine-containing segments were fixed by chemical bonding to improve the low surface energy of the coating and the interfacial compatibility between the coating and the substrate, forming a three-dimensional network structure with high cross-linking density.
It achieves excellent stain resistance to a variety of graffiti media. The graffiti media is easy to wipe off the coating surface. The coating does not run during long-term use and has high chemical stability and good adhesion, ensuring the integrity and washability of the coating.
Smart Images

Figure CN122587581B_ABST
Abstract
Description
Technical Field
[0001] This invention discloses a coating technology, and in particular relates to an art coating with an anti-graffiti and stain-resistant coating and its preparation method. Background Technology
[0002] UV-curable coatings offer advantages such as fast curing speed, low environmental pollution, and low energy consumption, and are widely used in coating substrates such as wood, plastics, metals, and glass. However, existing UV-curable colored coatings have the following technical drawbacks: First, their anti-graffiti performance is insufficient. Existing UV-cured coatings mainly rely on high cross-linking density and smooth surfaces to achieve a certain degree of stain resistance, but they lack effective resistance to graffiti media such as oil-based markers and spray paints. Graffiti media can wet and penetrate into the micropores of the coating surface, making them difficult to remove.
[0003] Secondly, organic pigments have poor weather resistance and interfere with UV curing. Most colored UV coatings use organic pigments, which are easily degraded and faded under ultraviolet radiation. At the same time, organic pigments have a strong absorption and scattering effect on ultraviolet light. When the coating thickness increases, the surface layer is prone to curing while the bottom layer is not.
[0004] Third, low surface energy modification technology has poor compatibility with UV curing systems. Fluorine- or silicon-containing low surface energy additives are widely used in traditional thermosetting or water-based systems, but in UV curing systems, the migration behavior of low surface energy components before curing is difficult to control, which can easily lead to problems such as uneven surface enrichment, pinholes, and decreased adhesion.
[0005] In addition, inorganic pigments have poor interfacial compatibility with UV resin matrices. Inorganic pigments are hydrophilic and have poor compatibility with hydrophobic acrylic resins, making them prone to agglomeration in the coating, which affects color uniformity and the mechanical properties of the coating.
[0006] Therefore, it is necessary to develop a UV-cured artistic coating that combines high decorativeness, high weather resistance, and excellent anti-graffiti and anti-fouling properties. Summary of the Invention
[0007] The purpose of this invention is to solve the above-mentioned problems by providing an art coating with an anti-graffiti and stain-resistant coating and its preparation method.
[0008] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing an art paint with an anti-graffiti and stain-resistant coating, comprising the following steps: S1, Inorganic pigment surface modification treatment: spinel type CoAl2O4 blue pigment is added to a high-speed disperser, and 3%-5% of γ-glycidyl etheroxypropyltrimethoxysilane by total pigment mass is added. The mixture is dispersed at 800-1000 r / min for 15-20 minutes, and then heated to 60-70°C and dispersed for another 30-40 minutes to obtain surface silanized modified inorganic pigment. S2, premixed coating: (1) Add epoxy acrylate resin and reactive diluent to a mixing container and stir at 300-400 r / min for 10-15 minutes until uniform; (2) Add silane-modified nano-silica slowly to the mixture obtained in step (1) under stirring, and disperse at a speed of 600-800 r / min for 20-30 minutes; (3) The inorganic pigment with surface silanization modification obtained in step S1 is slowly added to the slurry obtained in step (2) under stirring, and dispersed at high speed of 800-1000 r / min for 25-35 minutes. The temperature is controlled at 40-50°C during the dispersion process. (4) After premixing the fluorinated acrylate oligomer with an equal mass of tripropylene glycol diacrylate, add it dropwise to the slurry obtained in step (3) within 20-30 minutes. Stir at 400-500 r / min during the dropwise addition process, and continue stirring for 20-30 minutes after the dropwise addition is completed. (5) Add acryloyloxytrimethoxysilane, photoinitiator, amine accelerator, leveling agent and defoamer to the slurry obtained in step (4) in sequence, stir at 300-400 r / min for 15-20 minutes, and then filter with a 200-300 mesh sieve to obtain the artistic coating. S3: Coating and UV Curing The artistic coating obtained in step S2 is applied to a glass substrate, with the coating thickness controlled at 25-35 μm; ultraviolet curing is performed using a 1000W high-pressure mercury lamp, with a dominant wavelength of 365 nm and an irradiance of 80±10 mW / cm². 2 The radiation distance is 14-16cm, the radiation time is 55-65s, and it solidifies into a film in the air atmosphere.
[0009] As a preferred embodiment, in step S2 (4), the fluorinated acrylate oligomer is premixed with tripropylene glycol diacrylate and then added dropwise over a period of 25 minutes, with a stirring speed of 450 r / min during the addition process.
[0010] Preferably, in step S3, the coating thickness is 30 μm, the radiation distance is 15 cm, and the radiation time is 60 s.
[0011] Preferably, the preparation method of spinel-type CoAl2O4 blue pigment includes the following steps: K1, with the molar ratio of aluminum hydroxide to cobalt carbonate being 2.0:1.0-2.2:1.0, and the amount of boric acid added being 5.0%-6.0% of the total mass of aluminum hydroxide and cobalt carbonate, weigh out aluminum hydroxide, cobalt carbonate and boric acid respectively; K2, add the raw materials weighed in step K1 into a planetary ball mill, add zirconia grinding balls at a material-to-ball ratio of 1:3, add 15%-20% of the total mass of the raw materials as grinding media, and ball mill at a speed of 400-500 r / min for 4-6 hours. K3. Place the slurry after ball milling in step K2 in an electric heating constant temperature drying oven and dry it at 105-110°C for 12-16 hours to obtain the dried precursor. K4. Place the dried precursor obtained in step K3 into a corundum crucible, heat it to 1000-1100°C in a resistance furnace at a heating rate of 3-5°C / min, and calcine it for 3-4 hours. K5. After naturally cooling the product from step K4 to room temperature, add it back into a planetary ball mill. Add zirconia grinding balls at a material-to-ball ratio of 1:4, and add 20%-25% deionized water by weight of the product. Ball mill at 500-600 r / min for 6-8 hours to obtain a particle size D. 50 It is a spinel-type CoAl2O4 blue pigment with a particle size of 1.5-3.0 μm.
[0012] Preferably, the preparation method of silane-modified nano-silica includes the following steps: M1, nano-silica is dispersed in anhydrous ethanol to prepare a dispersion with a solid content of 10%-15%; M2, dissolve γ-glycidoxypropyltrimethoxysilane in anhydrous ethanol to prepare a solution with a concentration of 5%-10%, the amount of γ-glycidoxypropyltrimethoxysilane used is 15%-25% of the mass of nano silica; M3. Add the solution obtained in step M2 dropwise to the dispersion obtained in step M1. Stir at 300-400 r / min during the dropwise addition. Continue stirring for 30-40 minutes after the dropwise addition is complete. M4. Heat the mixture obtained in step M3 to 60-70°C and reflux for 4-6 hours. After the reaction is complete, M5 is centrifuged, washed 3-5 times with anhydrous ethanol, and vacuum dried at 80-100°C for 6-8 hours to obtain silane-modified nano-silica.
[0013] An art paint with an anti-graffiti and stain-resistant coating, prepared by the above-described method, comprises the following components by weight: 20-30 parts of epoxy acrylate resin, wherein the epoxy acrylate resin is epoxy 611 type epoxy acrylate resin with an acid value of 1.0-2.0 mgKOH / g; 20-30 parts of reactive diluent, which is a combination of trimethylolpropane triacrylate and tripropylene glycol diacrylate in a mass ratio of 5:3; 2-4 parts of photoinitiator, which is a combination of benzoin dimethyl ether and benzophenone in a 1:1 mass ratio; 1.5-2.5 parts of amine accelerator, wherein the amine accelerator is diethylamine; Spinel-type CoAl₂O₄ blue pigment, 3-7 parts. This spinel-type CoAl₂O₄ blue pigment is prepared by a solid-state method using aluminum hydroxide and cobalt carbonate as raw materials and boric acid as a mineralizing agent. The molar ratio of aluminum hydroxide to cobalt carbonate is 2.0:1.0-2.2:1.0. The amount of boric acid added is 5.0%-6.0% of the total mass of aluminum hydroxide and cobalt carbonate. The pigment particle size D... 50 Its thickness is 1.5-3.0 μm; 2-4 parts of silane-modified nano-silica, the original particle size of the nano-silica being 20-50 nm, are surface-modified with γ-glycidoxypropyltrimethoxysilane, the amount of which is 15%-25% of the mass of the nano-silica. 1-3 parts of fluorinated acrylate oligomer, wherein the fluorinated acrylate oligomer is a perfluorinated polyether acrylate with a molecular weight of 1800-2800 and a fluorine content of 35%-60%; 0.1-0.5 parts of γ-glycidyl oxypropyltrimethoxysilane; Acryloyloxytrimethoxysilane 1.5-2.5 parts; 0.3-0.7 parts of leveling agent, the leveling agent is BYK-300; 0.2-0.5 parts of defoamer, the defoamer is 5400-PⅡ.
[0014] Compared with the prior art, the beneficial effects of the present invention are: The artistic coating of this invention utilizes fluorinated acrylate oligomers to provide low surface energy and silane-modified nano-silica to construct a micro-nano dual rough structure. These two elements work synergistically to keep the graffiti medium in a Cassie-Baxter state, resulting in a small actual contact area and extremely low adhesion. Unlike physically added fluorinated additives such as PDMS, which migrate and bleed away, this invention uses chemical bonds in the fluorinated segments to firmly fix the coating, preventing loss during long-term use and wiping. Using CoAl2O4 spinel as a raw material, the structure exhibits extremely high chemical stability, superior to organic pigments. Furthermore, its transmittance in the 300-400nm ultraviolet region is higher than that of organic pigments. It does not interfere with UV curing; diethylamine effectively inhibits oxygen polymerization, and the combination of benzoin dimethyl ether and benzophenone improves photoinitiation efficiency. In addition, the use of inorganic pigments does not absorb ultraviolet light, ensuring complete curing of the 30μm thick film; the acryloyloxy group of KH-570 participates in UV polymerization, and the methoxysilane forms Si-O-Si chemical bonds with the silanol groups on the glass surface to achieve chemical bonding between the coating and the substrate; KH-560 silanizes the pigment surface, and the epoxy groups react with the resin to improve the compatibility of the pigment-resin interface. Through a stepwise gradient dispersion process, nano-SiO2 is dispersed first, then pigment, and finally low surface energy components to prevent agglomeration. Attached Figure Description
[0015] Figure 1 The chart shows the combined test results of Example 1 and Comparative Examples 1-4; Figure 2 The chart shows the stain resistance test results of various graffiti media in Example 1; Figure 3 The charts show the durability test and long-term anti-graffiti performance tracking test of the fluorinated component in Example 1; Figure 4 SEM images comparing spinel CoAl2O4 after sintering for 1 h and 4 h; Figure 5 The LAB colorimetric values of spinel CoAl2O4 at 1050℃ are shown. Figure 6 The image shows the XRD pattern of spinel CoAl2O4 at 1050℃. Detailed Implementation
[0016] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. In this description, it should be understood that the terms "upper," "lower," "front," "rear," "left," "right," "top," "bottom," "inner," and "outer," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0017] Example 1
[0018] A method for preparing an art paint with an anti-graffiti and stain-resistant coating, wherein the preparation of the raw material spinel-type CoAl2O4 blue pigment includes the following steps: K1, with a molar ratio of aluminum hydroxide to cobalt carbonate of 2.0:1.0, and boric acid added at 5.5% of the total mass of aluminum hydroxide and cobalt carbonate, weigh out 109.20g of aluminum hydroxide, 59.47g of cobalt carbonate and 9.26g of boric acid respectively; K2, add the above raw materials into a planetary ball mill, add zirconia grinding balls (grinding balls with diameters of 5mm and 10mm mixed at a mass ratio of 2:1) at a material-to-ball ratio of 1:3, add 18% of the total mass of the raw materials as grinding media, and ball mill at a speed of 450r / min for 5 hours. K3, the ball-milled slurry was placed in an electric thermostatic drying oven and dried at 108°C for 14 hours to obtain the dried precursor; K4, place the dried precursor in a corundum crucible, heat it to 1050°C in a resistance furnace at a heating rate of 4°C / min, and calcine it for 3.5 hours. K5, after naturally cooling the calcined product to room temperature, was added again to a planetary ball mill. Zirconia grinding balls were added at a material-to-ball ratio of 1:4, along with 22% (by weight of the product) of deionized water. The mill was then ball-milled at 550 r / min for 7 hours to obtain a particle size D. 50 It is a spinel-type CoAl2O4 blue pigment with a diameter of 2.2 μm.
[0019] like Figure 4The image shows a comparison of SEM images of spinel CoAl2O4 after sintering for 1 h and 4 h, with a sintering temperature of 1050℃. As shown in (a), when the reaction is incomplete, the pigment particle size is in the micrometer range, approximately 1-2µm. Small particles aggregate together to form large particles, exhibiting a certain degree of agglomeration. As shown in (c), with the extension of sintering time, the diffusion of each particle is more complete, the contact time is extended, the reaction is more complete, the composition of the pigment is uniform, and at the same time, the pigments are bonded together.
[0020] Figure 5 The LAB colorimetric values of spinel CoAl2O4 at 1050℃ are shown. Figure 6 The image shows the XRD pattern of spinel CoAl2O4 at 1050℃. With the extension of sintering time, the pigment brightness value L generally shows an increasing trend, but the change is very small; the pigment red hue value A gradually increases, reaching -4.04 when the sintering time is 8h; the pigment blue hue value B gradually decreases, reaching -47.43 when the sintering time is 8h, that is, the blue color gradually deepens. With the extension of sintering time, the relative intensity of each diffraction peak gradually increases, that is, the contact time of each particle in the system is longer and the reaction is more complete. In summary, the extension of sintering time can make the reaction more complete, and the resulting pigment brightness value L and red hue value A both increase, while the blue hue value B decreases, and the overall blue color is more vivid.
[0021] The preparation of silane-modified nano-silica includes the following steps: M1 contains 30g of nano-silica (original particle size 30nm, specific surface area 200m²). 2 / g, fumed nano-silica) was dispersed in 270g of anhydrous ethanol to prepare a dispersion with a solid content of 10%, and ultrasonically dispersed for 30 minutes. M2, dissolve 6g of γ-glycidoxypropyltrimethoxysilane (KH-560, purity ≥98%) in 60g of anhydrous ethanol to prepare a solution with a concentration of 9.1%.
[0022] M3. Add the KH-560 ethanol solution obtained in step M2 dropwise to the nano silica dispersion obtained in step M1. Stir at 350 r / min during the dropwise addition process, and continue stirring for 35 minutes after the dropwise addition is completed.
[0023] M4, heat the mixture to 65°C and reflux for 5 hours; After the reaction was completed, the mixture was centrifuged at 4000 r / min for 10 minutes, washed four times with anhydrous ethanol, and dried under vacuum at 90°C for 7 hours to obtain silane-modified nano-silica.
[0024] Thermogravimetric analysis (TGA) showed that the weight loss of the modified nano-silica was approximately 18.5%, indicating that KH-560 was successfully grafted onto the surface of the nano-silica. Laser particle size analysis showed that the dispersed particle size of the modified nano-silica in the acrylate resin was 35-50 nm, with no obvious agglomeration. Fluorinated acrylate oligomers are synthesized by the following method: Perfluoropolyether glycol (molecular weight 2000, fluorine content >30%) and acrylic acid (molar ratio 1:2.2) were reacted in toluene with p-toluenesulfonic acid catalyst (1% of the total mass of reactants) and hydroquinone (0.05%) as a polymerization inhibitor. The mixture was refluxed at 110°C for 8 hours. The water generated was removed by a water separator. After the reaction was completed, toluene and excess acrylic acid were removed by vacuum distillation to obtain perfluoropolyether-based acrylate oligomers. GPC analysis showed that the molecular weight was Mn=2200, Mw=2600, and PDI=1.18. 1 ¹H NMR analysis revealed characteristic peaks of acrylate double bonds at δ = 5.8-6.4 ppm, with the following structure: CF3(CF2CF2O) 10 CF2CH2OCH2CH2CH2O-CO-CH=CH2; The anti-graffiti art coating is prepared by weighing each component according to the following parts by weight: ; The preparation steps are as follows: S1: Add 5 parts of CoAl2O4 blue pigment to a high-speed disperser, add 0.2 parts of KH-560, disperse at 900 r / min for 18 minutes, heat to 65°C, and continue to disperse for 35 minutes to obtain surface silanized modified inorganic pigment.
[0025] S2: (1) Add 25 parts of epoxy acrylate resin, 15.625 parts of TMPTA and 9.375 parts of TPGDA to a mixing container and stir at 350 r / min for 12 minutes.
[0026] (2) Add 3 parts of silane-modified nano silica slowly and disperse at 700 r / min for 25 minutes.
[0027] (3) The surface silanized modified inorganic pigment obtained in step S1 is slowly added and dispersed at a high speed of 900 r / min for 30 minutes, while the temperature of the dispersion tank is controlled at 45°C.
[0028] (4) Premix 2 parts of perfluoropolyether acrylate oligomer with 2 parts of TPGDA and add them dropwise over 25 minutes. Stir at 450 r / min during the dropwise addition and continue stirring for 25 minutes after the dropwise addition is complete.
[0029] (5) Add 2 parts KH-570, 1.5 parts benzoin dimethyl ether, 1.5 parts benzophenone, 2 parts diethylamine, 0.5 parts BYK-300, and 0.3 parts 5400-PⅡ in sequence, stir at 350 r / min for 18 minutes, filter with a 250 mesh sieve to obtain the art paint.
[0030] S3: Apply the coating to the glass plate using a wire rod, controlling the wet film thickness to be 75μm and the dry film thickness to be approximately 30μm. Use a 1000W high-pressure mercury lamp (dominant wavelength 365nm, irradiance 80mW / cm²), irradiation distance 15cm, irradiation time 60s, and cure in air.
[0031] Design the following four sets of comparative examples: Comparative Example 1: Unmodified nano-silica Except for replacing the silane-modified nano silica in Example 1 with an equal amount of unmodified nano silica (original particle size 30nm, not modified by KH-560), the rest of the formulation and process are exactly the same as in Example 1; Comparative Example 2: Fluoro-free acrylate oligomers Except for omitting the perfluoropolyether-based acrylate oligomer, the formulation and process are exactly the same as in Example 1; Comparative Example 3: Using the organic pigment phthalocyanine blue Except for replacing the CoAl2O4 blue pigment with an equal amount of phthalocyanine blue (organic pigment, particle size D) 50 =0.3μm), and except for omitting the pigment surface treatment step (KH-560 is not added in step S1), the rest of the formulation and process are exactly the same as in Example 1; Comparative Example 4: Without KH-570 coupling agent Except for omitting KH-570, the rest of the formula and process are exactly the same as in Example 1; Uniform samples were prepared for performance testing. The pre-coated substrate was a colorless and transparent float glass plate with dimensions of 150mm×70mm×3mm. It was wiped with anhydrous ethanol to remove oil, rinsed with deionized water, and dried at room temperature. The coating was applied by wire rod coating (wet film thickness 75μm), and the dry film thickness was 30±2μm. After curing, the samples were tested after being cured at a temperature of 23±2°C and a relative humidity of 50±5% for 24 hours. Mechanical properties such as adhesion and scrub resistance were tested after curing for 7 days. The surface drying time test adopts the finger touch method according to GB / T1728-1979. The timing starts immediately after curing. The surface of the coating is lightly touched with a degreased cotton ball. The surface is considered to be dry if the cotton ball does not stick and the coating does not leave an indentation. A 1000W high-pressure mercury lamp is used with a radiation distance of 15cm and continuous radiation is performed. The time from the start of radiation to surface drying is recorded. The pendulum hardness is determined according to GB / T1730-1993, with a test environment of 23±2°C and 50±5%RH. For the König pendulum, the time it takes for the amplitude to decrease from 6° to 3° is measured for a length of 200mm. For the Persoz pendulum, the time it takes for the amplitude to decrease from 12° to 4° is measured, expressed as the pendulum damping time in seconds, or converted to relative hardness (with a glass value of 1.00). The adhesion test follows GB / T9286-1998, with a grid spacing of 1mm and a grid of 6×6. A single-edged cutter or a multi-functional cross-cutting tool is used. The test procedure is as follows: cut 6 parallel scratches on the coating film with uniform pressure, with a spacing of 1mm; then cut 6 more scratches vertically to form a grid; brush lightly 5 times along the diagonal with a soft brush; apply transparent pressure-sensitive tape (25mm wide, adhesion 10±1N) and quickly peel it off at a 60° angle. The contact angle test was conducted according to GB / T30693-2014. The test environment was 23±2°C, 50±5%RH, droplet volume was 2±0.5μL, drop height was 3mm, and an optical contact angle measuring instrument with a resolution of 0.1° was used. The seated drop method was adopted, and the image was calculated by Young-Laplace equation after image acquisition. During the test, the droplet was gently placed on the coating surface, and the image was acquired after standing for 10s. The measurement was performed 5 times at different positions on the same sample, and the average value was taken. The anti-graffiti performance test adopts ASTM D6578 / D6578M-13(2024), the test environment is 23±2°C, 50±5%RH, and the graffiti media are oil-based markers (black, Deli S550), water-based markers (red), ordinary white spray paint, and lipstick. The graffiti media are evenly written or sprayed on the coating surface. After the specified time, the coating is placed for 24 hours for oil-based markers, 2 hours for spray paint, and 24 hours for lipstick. The coating is wiped 10 times with a dry and clean cotton cloth or a slightly damp cotton cloth with a moisture content of 30% at a force of 5N. The residue is visually observed and graded as follows: completely erased: no trace; slight trace: slight trace, but not obvious; obvious trace: requires solvent wiping; cannot be erased: requires sanding or solvent soaking. The washability test was conducted according to GB / T9266-2009. The test environment was 23±2°C and 50±5%RH. The washing medium was 0.5% soap solution. The brush size was 38mm×90mm, the load was 450±2g, the reciprocating frequency was 37±2 times / min, and the stroke was 300mm.
[0032] Test result charts are as follows Figure 1 As shown in the test results, it can be seen that: (1) Example 1 performed best in all test items: surface drying time 20s, pendulum hardness 0.68, adhesion grade 1, water contact angle 115°, oleic acid contact angle 82°, oil-based marker graffiti can be completely erased without residue, and washability exceeds 8000 times. (2) Comparative Example 1 (unmodified nano silica): Since the nano silica is unmodified, it has poor compatibility with the resin and slightly agglomerates in the coating, resulting in a slightly grainy coating. The water contact angle drops to 105°, the oleic acid contact angle is only 68°, the anti-graffiti performance decreases, and the scrub resistance decreases to 6500 cycles. This proves that silane-modified nano silica is crucial for dispersibility and anti-graffiti performance. (3) Comparative Example 2 (without fluorinated acrylate oligomer): Although the curing speed and hardness were good, the water contact angle dropped to 95° and the oleic acid contact angle was only 55°. Oil-based marker graffiti left obvious marks that could only be removed by wiping with solvent, proving that fluorinated acrylate oligomer is the key component that gives the coating excellent anti-graffiti properties. (4) Comparative Example 3 (organic pigment phthalocyanine blue): The surface drying time was extended to 35s, the hardness of the pendulum rod decreased to 0.52, and the coating film was not fully cured due to the absorption of ultraviolet light by the organic pigment, resulting in surface curing and stickiness of the bottom layer. The adhesion decreased to level 2, proving that the use of inorganic pigments is crucial to the curing efficiency and coating performance of the UV curing system. (5) Comparative Example 4 (without KH-570): Although the anti-graffiti performance was good, the adhesion dropped to level 4 and the coating was easy to fall off, proving that KH-570 is essential to improve the adhesion between the coating and the glass substrate.
[0033] The coating of Example 1 was subjected to stain resistance tests on various graffiti media, and the test results are as follows: Figure 2 As shown, the results indicate that the coating of Example 1 has excellent resistance to various graffiti media, including oil-based, water-based, and solid graffiti media. The graffiti media appears as beads or flakes on the coating surface, which are easy to wipe off and leave no trace. The coating of Example 1 was subjected to durability tests of the fluorine-containing components and long-term anti-graffiti performance tracking tests, and the results are as follows: Figure 3 As shown, the test environment was 23±2°C and 50±5%RH. The results showed that the fluorinated acrylate oligomer in the coating of Example 1 was fixed in the coating network by chemical bonding. Under long-term UV aging and hot water immersion conditions, the low surface energy properties remained stable and the anti-graffiti properties did not significantly decrease.
[0034] Example 1 features a low surface energy repulsion mechanism. The perfluoropolyether segments on the coating surface have extremely low surface tension, far lower than that of common graffiti media. According to wetting theory, when the surface energy of the coating is lower than the surface tension of the graffiti media, the graffiti media is difficult to spread on the coating surface, forming a large contact angle, which can effectively repel water and oily media. The introduction of fluorinated acrylate oligomers significantly improves the contact angle of the coating against oily media. The key is that the fluorinated acrylate oligomers used contain acrylate double bonds, which are chemically bonded to the three-dimensional network of the coating through free radical polymerization during UV curing. The perfluoropolyether segments are directionally enriched on the coating surface, forming a stable low surface energy layer. This is fundamentally different from physically added fluorinated additives that are easily migrated and lost. It is also the result of QUV 3000h aging. The reason why the anti-graffiti performance remains stable after coating is that the silane-modified nano-silica (original particle size 20-50nm, dispersed particle size 35-50nm in resin) in the coating, with the micro-nano rough structure enhancement mechanism, together with the micron-sized pigment particles, constructs a micro-nano double rough structure. When the surface energy of the coating is low enough, this rough structure can put the graffiti medium in a Cassie-Baxter state: air is trapped between the droplets and the coating, which greatly reduces the actual contact area and significantly increases the apparent contact angle. The graffiti medium is attached in bead or hemispherical shape and is easy to wipe off. The use of silane-modified nano-SiO2, which is uniformly dispersed in acrylate resin, synergistically forms a uniform micro-nano double rough structure with the pigment particles, increasing the oleic acid contact angle to 82°, achieving complete wiping. This indicates that silane modification and uniform dispersion of nano-SiO2 are prerequisites for constructing an effective rough structure; it has a high cross-linking density barrier mechanism, using trifunctional epoxy acrylate resin compounded with trifunctional TMPTA and difunctional TPGDA, forming a highly cross-linked three-dimensional network structure after UV curing. The high cross-linking density reduces the free volume of the coating, making it difficult for the graffiti medium to penetrate into the coating and only stay on the coating surface.Compared to organic pigments, which strongly absorb ultraviolet light, leading to incomplete curing of the underlying layer, a decrease in pendulum hardness to 0.52, and a significant reduction in the washability and anti-graffiti properties of the coating, the spinel-type CoAl2O4 inorganic pigment used in Example 1 has high transmittance in the 300-400nm ultraviolet region, does not interfere with UV curing, and ensures that the coating achieves a uniform high crosslinking density. The synergistic effect of the three mechanisms means that neither low surface energy alone nor micro-nano rough structure alone can completely prevent the wetting and adhesion of oil-based markers. However, Example 1 combines low surface energy, micro-nano rough structure, and high crosslinking density to produce an anti-graffiti effect that cannot be achieved by a single mechanism. This synergistic effect is specifically manifested in the fact that the fluorinated acrylate oligomer provides low surface energy, resulting in a larger initial contact angle of the graffiti medium. The micro-nano rough structure further increases the contact angle and reduces the actual contact area through the Cassie-Baxter effect; the high cross-linking density prevents the penetration of graffiti media, ensuring that graffiti only stays on the surface. The three work together to make the coating exhibit excellent resistance to various graffiti media such as oil-based markers, spray paint, and lipstick. For the practical application of anti-graffiti coatings, the problem of coating film not falling off when wiping still needs to be solved. The chemical bonding between the coating and the glass substrate is achieved by acryloyloxytrimethoxysilane (KH-570): the acryloyloxy group of KH-570 participates in UV free radical polymerization, and the methoxysilane group reacts with the silanol group on the glass surface to form Si-O-Si bonds. The coating film remains intact when repeatedly wiped and graffitied, and the anti-graffiti function can be performed for a long time.
[0035] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No reference numerals in the claims should be construed as limiting the scope of the claims.
[0036] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. A method for preparing an art paint with an anti-graffiti and stain-resistant coating, characterized in that, Includes the following steps: S1, Inorganic pigment surface modification treatment: Add spinel-type CoAl2O4 blue pigment to a high-speed disperser, add 3%-5% of γ-glycidyl etheroxypropyltrimethoxysilane by weight of the pigment, disperse at 800-1000 r / min for 15-20 minutes, then heat to 60-70°C and continue dispersing for 30-40 minutes to obtain surface silanized modified inorganic pigment. S2, premixed coating: (1) Add epoxy acrylate resin and reactive diluent to a mixing container and stir at 300-400 r / min for 10-15 minutes until uniform; (2) Add silane-modified nano-silica slowly to the mixture obtained in step (1) under stirring, and disperse at a speed of 600-800 r / min for 20-30 minutes; (3) The inorganic pigment with surface silanization modification obtained in step S1 is slowly added to the slurry obtained in step (2) under stirring, and dispersed at high speed of 800-1000 r / min for 25-35 minutes. The temperature is controlled at 40-50°C during the dispersion process. (4) After premixing the fluorinated acrylate oligomer with an equal mass of tripropylene glycol diacrylate, add it dropwise to the slurry obtained in step (3) within 20-30 minutes. Stir at 400-500 r / min during the dropwise addition process, and continue stirring for 20-30 minutes after the dropwise addition is completed. (5) Add acryloyloxytrimethoxysilane, photoinitiator, amine accelerator, leveling agent and defoamer to the slurry obtained in step (4) in sequence, stir at 300-400 r / min for 15-20 minutes, and then filter with a 200-300 mesh sieve to obtain the artistic coating. S3, Coating and UV Curing: The artistic coating obtained in step S2 is applied to a glass substrate, with the coating thickness controlled at 25-35 μm; ultraviolet curing is performed using a 1000W high-pressure mercury lamp, with a dominant wavelength of 365 nm and an irradiance of 80±10 mW / cm². 2 The radiation distance is 14-16cm, the radiation time is 55-65s, and it solidifies into a film in the air atmosphere.
2. The method for preparing an art paint with an anti-graffiti and stain-resistant coating according to claim 1, characterized in that, In step S2(4), the fluorinated acrylate oligomer is premixed with tripropylene glycol diacrylate and then added dropwise over a period of 25 minutes. During the addition process, the stirring speed is 450 r / min.
3. The method for preparing an art paint with an anti-graffiti and stain-resistant coating according to claim 1, characterized in that, In step S3, the coating thickness is 30 μm, the radiation distance is 15 cm, and the radiation time is 60 s.
4. The method for preparing an art paint with an anti-graffiti and stain-resistant coating according to claim 1, characterized in that, The preparation method of spinel-type CoAl2O4 blue pigment includes the following steps: K1, with the molar ratio of aluminum hydroxide to cobalt carbonate being 2.0:1.0-2.2:1.0, and the amount of boric acid added being 5.0%-6.0% of the total mass of aluminum hydroxide and cobalt carbonate, weigh out aluminum hydroxide, cobalt carbonate and boric acid respectively; K2, add the raw materials weighed in step K1 into a planetary ball mill, add zirconia grinding balls at a material-to-ball ratio of 1:3, add 15%-20% of the total mass of the raw materials as grinding media, and ball mill at a speed of 400-500 r / min for 4-6 hours. K3. Place the slurry after ball milling in step K2 in an electric heating constant temperature drying oven and dry it at 105-110°C for 12-16 hours to obtain the dried precursor. K4. Place the dried precursor obtained in step K3 into a corundum crucible, heat it to 1000-1100°C in a resistance furnace at a heating rate of 3-5°C / min, and calcine it for 3-4 hours. K5. After naturally cooling the product from step K4 to room temperature, add it back into a planetary ball mill. Add zirconia grinding balls at a material-to-ball ratio of 1:4, and add 20%-25% deionized water by weight of the product. Ball mill at 500-600 r / min for 6-8 hours to obtain a particle size D. 50 It is a spinel-type CoAl2O4 blue pigment with a particle size of 1.5-3.0 μm.
5. The method for preparing an art paint with an anti-graffiti and stain-resistant coating according to claim 4, characterized in that, The preparation method of silane-modified nano-silica includes the following steps: M1, nano-silica is dispersed in anhydrous ethanol to prepare a dispersion with a solid content of 10%-15%; M2, dissolve γ-glycidoxypropyltrimethoxysilane in anhydrous ethanol to prepare a solution with a concentration of 5%-10%, the amount of γ-glycidoxypropyltrimethoxysilane used is 15%-25% of the mass of nano silica; M3. Add the solution obtained in step M2 dropwise to the dispersion obtained in step M1. Stir at 300-400 r / min during the dropwise addition. Continue stirring for 30-40 minutes after the dropwise addition is complete. M4. Heat the mixture obtained in step M3 to 60-70°C and reflux for 4-6 hours. After the reaction is complete, M5 is centrifuged, washed 3-5 times with anhydrous ethanol, and vacuum dried at 80-100°C for 6-8 hours to obtain silane-modified nano-silica.
6. An art paint with an anti-graffiti and stain-resistant coating, characterized in that, Prepared by the preparation method according to any one of claims 1-5, and comprising the following components by mass parts: 20-30 parts of epoxy acrylate resin, wherein the epoxy acrylate resin is epoxy 611 type epoxy acrylate resin with an acid value of 1.0-2.0 mgKOH / g; 20-30 parts of reactive diluent, which is a combination of trimethylolpropane triacrylate and tripropylene glycol diacrylate in a mass ratio of 5:3; 2-4 parts of photoinitiator, which is a combination of benzoin dimethyl ether and benzophenone in a 1:1 mass ratio; 1.5-2.5 parts of amine accelerator, wherein the amine accelerator is diethylamine; Spinel-type CoAl₂O₄ blue pigment, 3-7 parts. This spinel-type CoAl₂O₄ blue pigment is prepared by a solid-state method using aluminum hydroxide and cobalt carbonate as raw materials and boric acid as a mineralizing agent. The molar ratio of aluminum hydroxide to cobalt carbonate is 2.0:1.0-2.2:1.
0. The amount of boric acid added is 5.0%-6.0% of the total mass of aluminum hydroxide and cobalt carbonate. The pigment particle size D... 50 Its thickness is 1.5-3.0 μm; 2-4 parts of silane-modified nano-silica, the original particle size of the nano-silica being 20-50 nm, are surface-modified with γ-glycidoxypropyltrimethoxysilane, the amount of which is 15%-25% of the mass of the nano-silica. 1-3 parts of fluorinated acrylate oligomer, wherein the fluorinated acrylate oligomer is a perfluorinated polyether acrylate with a molecular weight of 1800-2800 and a fluorine content of 35%-60%; 0.1-0.5 parts of γ-glycidyl oxypropyltrimethoxysilane; Acryloyloxytrimethoxysilane 1.5-2.5 parts; 0.3-0.7 parts of leveling agent, the leveling agent is BYK-300; 0.2-0.5 parts of defoamer, the defoamer is 5400-PⅡ.
Citation Information
Patent Citations
UV curing coating composition, preparation method thereof and blackboard
CN118755380A
CoAl2O4 pigment containing colar coating agent forcorrosion resistance and preparation method of thereof
KR1020060021752A
